Horrible British Histories: Young people in museums interrogating national identity through principles and practices of critical pedagogy - Habib, Sadia (PRISM: Casting New Light on Learning, Theory and Practice, 2021)
This paper explores the importance of supporting young people in exploring identities and belongings in the cultural heritage sector. When working with young people in British museums, creating open and safe spaces for discussing the entanglements of contemporary multicultural identities with the legacies of British colonialism is necessary and long overdue.  By employing the principles and practices of critical pedagogy, heritage organisations can interrogate the dominant narratives about identity and belonging in Britain, and work with young people to highlight shifting, fluid and multiple identities and belongings in contemporary Britain.Drawing on my experiences as the Our Shared Cultural Heritage Project Coordinator at Manchester Museum, I argue the case for cultural and heritage institutions to create safe spaces for young people from diverse ethnic and class backgrounds to explore and celebrate the meanings and complexities of their lived experiences of Britishness. Museums can become crucial cultural sites where young people can lead a critical interrogation of the idea of nation, through an exploration of the discourses attached to British identities that play out at local, national and global levels.  Critical pedagogy is an emancipatory and transformative approach to democratising education, and we urgently need more of it in museums to radically transform heritage spaces.